Relative bioavailability of prasugrel free base in comparison to prasugrel hydrochloride in the presence and in the absence of a proton pump inhibitor - Seiler, Dan; Doser, Karlheinz; Salem, Isam (Arzneimittelforschung, 2011)
Prasugrel (CAS 150322-43-3), an inhibitor of platelet activation and aggregation, is indicated to reduce the rate of thrombotic cardiovascular events in patients with acute coronary syndrome. If a proton pump inhibitor is co-administered with prasugrel, a pH dependent salt-to-base conversion rate of prasugrel could become clinically meaningful. In an open-label, randomized, four-period, 2 × two-way crossover study, the relative bioavailability of tablets containing prasugrel free base compared to prasugrel hydrochloride (originator product) both in the presence and in the absence of the proton pump inhibitor lansoprazole (CAS 103577-45-3) was investigated. In the absence of lansoprazole, the extent of absorption (AUC) of prasugrel free base was about 8–9 % lower, while the rate of absorption (Cmax) after administration of prasugrel free base was 20 % lower when compared to prasugrel hydrochloride. When lansoprazole was used to raise the pH level in the upper gastro-intestinal tract, AUC was decreased by 25 % after administration of prasugrel hydrochloride and by 41 % after prasugrel free base. In addition, the peak plasma levels were decreased by 52 % and 72 %, respectively (geometric means). The relative bioavailability of the prasugrel free base compared to prasugrel hydrochloride, both in the presence and in the absence of the proton pump inhibitor lansoprazole, differs so much that most probably a generic formulation containing prasugrel free base will not be equivalent in all aspects to the originator product.
Keywords: Bioavailability; Interaction; Lansoprazole; Platelet aggregation inhibitor; Prasugrel; Proton pump inhibitor